Oil drop face mask for sinus relief - Nur Hanisah Razali; Faten Elina Kamaruddin; Ainol Mardhiyah Rahmat; Nur Rifhan A. Rahim; Siti Noorhaslina Abd Halim; Hafizuddin Md Dali; Muhammad Haris Naqiuddin Muda (Malaysia Journal of Invention and Innovation)
: Acute sinusitis is an infection caused by a virus that can lead to a congested or blocked nose, pain or pressure around your face, head, and eyes, loss of smell and taste, bad breath, ear pain, and headache. This common occurrence which has impacted about 14% of the general population happens due to the bacteria and viruses settling in the sinuses. Malaysia Statista reports that each person is expected to use 0.21 pieces of face mask in the year 2024 and is expected to be virus-killing, eco-friendly, and reusable. Through the idea and innovation of face masks, this study innovates sinus relief face masks. Sinus relief face masks are a combination of face masks with oil drops extracted from ingredients such as lemongrass, cinnamon, garlic, turmeric, ginger, and clove. This product aims to provide relief for those suffering from sinusitis while consolidating the elements of remediation and essential. With innovative features and differentiation, this product further bolsters growth potential. The extensive distribution reach enables broad customer access and high customer retention. This product aims for commercial success in the sinusitis relief market.